Slavery by any other name : African life under company rule in colonial Mozambique - Allina, Eric (Reconsiderations in southern African history., 2012)
Based on documents from a long-lost and unexplored colonial archive, Slavery by Any Other Name tells the story of how Portugal privatized part of its empire to the Mozambique Company. In the late nineteenth and twentieth centuries, the company governed central Mozambique under a royal charter and built a vast forced labor regime camouflaged by the rhetoric of the civilizing mission. Oral testimonies from more than one hundred Mozambican elders provide a vital counterpoint to the perspectives of colonial officials detailed in the archival records of the Mozambique Company. Putting elders' voices into dialogue with officials' reports, Eric Allina reconstructs this modern form of slavery, explains the impact this coercive labor system had on Africans' lives, and describes strategies they used to mitigate or deflect its burdens. In analyzing Africans' responses to colonial oppression, Allina documents how some Africans succeeded in recovering degrees of sovereignty, not through resistance, but by placing increasing burdens on fellow Africans--a dynamic that paralleled developments throughout much of the continent. This volume also traces the international debate on slavery, labor, and colonialism that ebbed and flowed during the first several decades of the twentieth century, exploring a conversation that extended from the backwoods of the Mozambique-Zimbabwe borderlands to ministerial offices in Lisbon and London. Slavery by Any Other Name situates this history of forced labor in colonial Africa within the broader and deeper history of empire, slavery, and abolition, showing how colonial rule in Africa simultaneously continued and transformed past forms of bondage.